👤

Bonjour j'aurai besoin t'aide svp
factorise les expressions suivantes
A.(x-3) (2x+1) + (x-3) (5x-7)
B.(5x-6) (11x+6) + 8(11x+6)
C.(7x au carré - 5) (3x+9) + (7x-12) (3x+9)


Répondre :

Réponse :

Explications étape par étape

Bonjour

factorise les expressions suivantes

A.(x-3) (2x+1) + (x-3) (5x-7)

A = (x - 3)(2x + 1 + 5x - 7)

A = (x - 3)(7x - 6)

B.(5x-6) (11x+6) + 8(11x+6)

B = (11x + 6)(5x - 6 + 8)

B = (11x + 6)(5x + 2)

C.(7x au carré - 5) (3x+9) + (7x-12) (3x+9)

C = (3x + 9)(7x^2 - 5 + 7x - 12)

C = (3x + 9)(7x^2 + 7x - 17)

C = 3(x + 3)(7x^2 + 7x - 17)

Réponse :

bonjour

Explications étape par étape

A.(x-3) (2x+1) + (x-3) (5x-7)

(x-3)(2x+1+5x-7)

(x-3)(7x-6)

B.(5x-6) (11x+6) + 8(11x+6)

(11x+6)(5x-6+8)

(11x+6)(5x+2)

C.(7x² - 5) (3x+9) + (7x-12) (3x+9)

(3x+9)(7x²-5+7x-12)

3(x+3)(7x²+7x-17)